Development Of Motor Ability In Children With Low Birth Weight History In Mamuju District - Supratti Supratti; Iqra S (poltekkes kemenkes mataram, 2020)
Improving the quality of Human Resources (HR) through stimulation of growth and development in children aged under two years (0-24 months), needs to be a priority concern of parents / caregivers considering this period is called the